Developments in Science and Technology Can Influence Youth’s Style and Pancasila Ethics in Indonesian Society - Sekar Anggraini (International Journal of Students Education, 2024)
The increasing decline in morals and ethics in society is due to the increasing development of technology in the world. Where the content contained in it greatly influences the formation of people’s character, especially for young people and the next generation. Therefore, this research was carried out so that the younger generation can be wiser in using developments in science and technology and not view that science and technology are trivial and do not need to be considered in character formation and lifestyle. The purpose of this article is to find out to what extent the Pancasila ethics apply to millennials or the current younger generation. The results of this research prove that science and technology is very influential on the formation of the character of the younger generation which includes morals and ethics and this research also proves that science and technology media is very closely related to society, especially the younger generation and is very difficult to separate, but science and technology is also like a double-edged sword because if they cannot use it well then they will fall in the wrong direction which will cause their morals and ethics to decline further and if they can use it well then they will have a wide network in society. Study This use approach qualitative descriptive, that is something method study Which used For study condition, situation, ideology and incident social on era we. Source data Which usedin this research is a literature study, that is source data primary or secondary.